PENGGUNAAN MEDIA TEKA-TEKI SILANG TERHADAP HASIL BELAJAR MATA PELAJARAN GEOGRAFI DI SMA NEGERI 1 SUNGAI RAYA - Rani Fadhila; Nuraini Asriati; Nur Meily Adlika (Universitas Tanjungpura, 2022)
The purpose of this study is to examine the impact of crossword media on student achievement in Geography IPS Class XI at SMA Negeri 1 Sungai Raya. This kind of research uses a quasi-experimental design with a pre- and post-test for two different groups. The participants were eleventh-grade IPS students. A simple random sampling technique from probability was used to choose the sample. The XI IPS 5 class served as the experimental group, while the XI IPS 3 class served as the control group. Crosswords were included into the therapeutic sessions for the test group but were not utilized with the XI IPS 3 control group. A rise from 50.71 to 67.11 was found to be the average for the control group in the statistical analysis. Based on the data collected, we can see that the experimental group's mean score increased from 39.00 on the pretest to 69.57 on the posttest. Under the null hypothesis of equal variances, SPSS's independent sample t-test analysis yields a t value of -6,274 and a p-value of 0.00 0.05, indicating that H0 cannot be accepted. Class XI IPS students at SMA Negeri 1 Sungai Raya may benefit from practicing crossword puzzles to increase their geographical knowledge, thus this sort of media is advised.